Pendidikan Agama Islam sebagai Basis Penguatan Sikap Patriotisme: Studi Kasus di SMA Kemala Bhayangkari 1 Surabaya Jawa Timur - Moh. Fatkur Rohman; Tasman Hamami (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2021)
The development of science and technology, as well as the ease of access to information, can have a negative impact on people's attitudes and behavior, including the phenomenon of the diminishing patriotism of the younger generation. An attitude of patriotism is the initial foundation for state life and becomes the joints of life in the daily life of citizens. This study examines Islamic Religious Education as a basis for strengthening students' patriotism attitudes. This study aims to describe and demonstrate the role of Islamic Religious Education in strengthening students' patriotism attitudes. This study was conducted at Kemala Bhayangkari 1 Senior High School Surabaya using a qualitative approach. Data collection was carried out through observation and in-depth interviews. The results showed that Islamic Religious Education contains teachings and values ​​that strengthen students' patriotism. Strategies for strengthening patriotism in Islamic Religious Education through exemplary advice and habituation in everyday life at school. This Islamic Religious Education Model is an alternative solution to arouse students' patriotism.